STEM Based Learning to Create Joyful Investigating Pumpkins for Mathematical Learning on Primary School - Ghenny Aosi (invotek, 2019)
This article was based on the results of classroom action research of STEM approach in investigating pumpkins at first grade of SDN 02 Aur Kuning Kota Bukittinggi. The students learn to know deeply about pumpkins that easily found in their sorrounding by investigating and combining science, mathematic, enggineering, drawing, and art in their learning process. The subject of this project was the first grader of 02 Aur Kuning elementary school students in Kota Bukittinggi. The methode used classroom action research methode in two cycles with two meeting per each cylce. Indikator of critical thinking that used in this study were basic operations of reasoning and metacognitive knowledge. The results of this research showed that by applying STEM approach in investigating pumpkin improved the learning outcome and students creative thinking in learning science and mathematic at elementary school in Bukittinggi.